Influence of Job Satisfaction and Organisational Commitment on Employee Turnover Intention in the Chemical Industry in South Africa - Masindi, Thiathu; Onojaefe, Darlington Peter; Tengeh, Robertson; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2024)
The study aimed to assess the extent to which work satisfaction and organisational commitment influence employee turnover, both individually and concurrently. The assessment was conducted quantitatively through the utilisation of an online survey approach to gather data from a sample of 249 respondents who were randomly chosen from the organisation operating in the specialty chemical business. The study discovered a detrimental absence of connection between employees and supervisors, which contributes to a climate of job unhappiness among the participants. Compared to other characteristics that have an influence, a lack of strong dedication to the organisation (known as affective commitment) resulted in an increased inclination to resign from the company. The study's findings suggest that an increase in job satisfaction and organisational commitment leads to a decrease in turnover intention. The supervisor's influence and emotional dedication to the organisation are recognised as being more substantial than other aspects. Consequently, research has shown that contentment with a colleague, manager, and client (in descending order) has a beneficial impact on affective commitment. Consequently, heightened levels of work satisfaction and organisational commitment results in a reduction in turnover intention. The study shows that employees' overall happiness with their supervisors, colleagues, and customers is associated with a decrease in their intention to leave the company, indicating a higher likelihood of retention.